The Number of Vaginal Epithellial and Neutrophil Strongly Correlates with the Occurrence of Premature Delivery - Alia Sandra (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To investigate the relationship of the amount of vagina epithelia and neutrophil with premature delivery. The study was carried out in several hospitals at Obstetrics and Gynecology Department of the Faculty of Medicine Hasanuddin University, from September 2011 to January 2012. Methods: The study was cross-sectional study involving two groups of sample: premature delivery group fulfilling inclusive criteria and a control group of normal delivery. The total samples are 48 persons, comprising of 16 premature deliveries, and 32 normal pregnancy. Result: The study revealed that there was a significant correlation between â‰¥1 parity and premature delivery (p<0.05). The average vagina epithelia in the premature delivery were 6.81 per field of view and in the normal pregnancy were 1.59 per field of view (p<0.001). The average vagina neutrophil in the premature delivery was 10.6 per field of view and in the normal pregnancy was 1.91 (p<0.001). Spearman correlation test showed that the vagina epithelia and neutrophil have a significant correlation with premature delivery as reflected by the coefficient correlation values of 0.907 and 0.770 with p=0.000. Conclusion: The number of ephitelia and vagina neutrophil in the premature delivery is higher than normal pregnancy, thus there is a strong correlation between number of ephitelia and vagina neutrophil and premature delivery. [Indones J Obstet Gynecol 2013; 37-2: 82-5] Keywords: epithelia, neutrophil, premature delivery